Frugal Living Lifestyle Of Millennial Family Couples In Aceh Tamiang - Anggi Maulida; Muhammad Iqbal (PT. Padang Tekno Corp, 2026)
This study aims to review the Frugal Living Lifestyle of Millennial Couples in Aceh Tamiang. It can be concluded that making collective spending decisions is crucial for family financial stability and achieving long-term goals. By involving all family members in planning, budget allocation, and regular evaluation, each expenditure can be more focused, priorities become clear, and financial responsibility becomes more evenly distributed. In addition to financial benefits, this habit also instills the values of cooperation, communication, and discipline in all family members, including children, thus establishing a healthy financial culture and strengthening family relationships.